2010
DOI: 10.1097/jto.0b013e3181c0a1f8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Histopathological Evaluation Method Predicting the Outcome of Non-small Cell Lung Cancer Treated by Neoadjuvant Therapy: The Prognostic Importance of the Area of Residual Tumor

Abstract: Smaller ART and p (-) predict a better outcome of NSCLC treated by neoadjuvant therapy. We concluded that ART is a novel histopathological evaluation method for predicting the outcome of NSCLC treated by neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 24 publications
3
39
2
Order By: Relevance
“…According to the previous studies [19,22], the percentage of viable tumor cells predicted better OS and DFS in NSCLC patients treated with neoadjuvant CTx even when pathologic stage was controlled. In another study, smaller area of residual tumor had correlation with better OS, also consistent with our study result [16].…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the previous studies [19,22], the percentage of viable tumor cells predicted better OS and DFS in NSCLC patients treated with neoadjuvant CTx even when pathologic stage was controlled. In another study, smaller area of residual tumor had correlation with better OS, also consistent with our study result [16].…”
Section: Commentsupporting
confidence: 93%
“…For patients receiving neoadjuvant chemotherapy (CTx) or CCRT for locally advanced NSCLC, there is abundant information on histopathologic factors establishing their role in the prediction of tumor response and patient survival [6,7,[10][11][12][13][14][15][16][17][18][19]. In contrast, the predictive value of imaging factors after neoadjuvant therapy for patients' OS and recurrence is still controversial and has been discussed in only a few studies [20][21][22].…”
Section: Introductionmentioning
confidence: 95%
“…When absolute OPN and GTV values were evaluated in multivariate an analysis, we found baseline OPN (t0) and GTV1 before RT as well as OPN at the end of RT (t1) and GTV2 (after 40 Gy) to be independent predictors of OS in different prognostic models. These results amend current literature such as the work of Yamane et al (25) who reported residual tumor volume after neoadjuvant chemotherapy of NSCLC to be prognostic, contrasting the results of Koo et al (14) who did not find a prognostic significance of post-RT GTV in the CCRT of NSCLC.…”
Section: Opn T0 To T1 ----------------------------------------------contrasting
confidence: 57%
“…11 Several small studies have suggested that the degree of tumor regression after neoadjuvant therapy as determined by histopathologic findings in the resected tumor may be a more objective criterion of chemotherapy response (Table 4). 1215 Our data on 192 patients with NSCLC treated with neoadjuvant chemotherapy suggest that the percentage of viable tumor cells does indeed predict OS even when controlled for pathologic stage. Importantly, in patients who are not treated with neoadjuvant chemotherapy (Table 2), the percentage of viable tumor cells is not predictive of OS.…”
Section: Discussionmentioning
confidence: 92%